The Power of Detailed Evidence as a Base on Land Rights - Ulfa Nisrina Sahib; Andi Suryaman Mustari Pide; Muhammad Ilham Arisaputra; Faharudin Faharudin (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
The strength of the proof of detail as the basis for land rights. This study was conducted to analyze the position of the detail as the basis for land rights in proving community ownership of land and to analyze the legal protection of land tenure by the community based on the detail as the basis for their rights. This research uses empirical legal research. The results of the study show that (1) the position of detail as the basis for land rights in proving land ownership by the community, namely before the issuance of the UUPA, detail was proof of ownership of land rights. Along with the enactment of the UUPA and Government Regulation Number 24 of 1997 concerning Land Registration, the Details are no longer as evidence of land rights, but as evidence of a person's control over the controlled land, so that if it is not corroborated with other evidence, the Details cannot be used absolutely as a tool. proof of ownership of land in the trial; and (2) legal protection of land tenure by the community based on details as the basis for their rights, namely that they have not yet fully received legal protection. So that in order to obtain legal certainty and protection.